Anti-corruption discourse and institutional change in Serbia: The money in Cyprus scandal - Zurnić Marija (Filozofija i Društvo, 2013)
This paper focuses on the scandal that occurred in 2001 during the intensive investigation of the financial transfers from Serbia to Cyprus during the 1990s. The paper looks at the strategies employed by politicians, practitioners and civil servants to achieve their political agendas. The findings prove that most actors take one of the following positions. They either share information about corruption scandals with the public in order to gain legitimacy for anti-corruption action, or they coordinate their joint response and avoid talking about the scandals in order to reduce political costs.